A review of the short story collection of Neelamalai - S, Aruchamy (International Research Journal of Tamil, 2021)
Review of the collection of short stories 'Neelamalai' written by Malayalam writer Urubu One of the notable writers in the world of Malayalam literature, PC Kuttikrishnan, also known as uhd Urubu, wrote a collection of short stories called 'Neelamalai' by. Kuttikrishna Menon is the whole point of Asha php. ‘Urubu’ is his nickname. Eva was born on June 8, 1915 in Ponnani, Kozhikode district. Evangel, Short Story, Drama, Poetry, as has given reassurance to all departments. MP Milk Award. Government of Kerala Award for Best Screenplay. Sahitya Akademi Award. The teacher sometimes lived in the Nilgiris and Wayanad hills, Short story Ava has said. There are a total of 6 short stories in this collection. The titles are set in relation to the central theme of the story. As the stories are centered on the Nilgiris and Wayanad, the technique of setting the beginning of the story with descriptions of places is used in all the stories. The characters in these stories are mostly hill people. Mountain races like Thotawa, Vaduga are shown. On a small scale vulgaris, gpw are shown as human beings. The hill tribesmen who come in male roles are hard workers. He has a hard working body and an owl mind that does not know the outside world. The women who come as female characters are innocent who do not know the outside world. So that he is deceived by others and, cannot break the rules. The characters, who are vulgar and, civilized, plunder the labor and life of the hill people. Pure Malayalam language is used in the stories. The vernacular is also used in the conversation of the hill tribes. vadugha language. Since the stories become the author's experience, it seems to be the best strategy to have the stories set by the teacher. The story is set in the Nilgiris, Wayanad hills, their biographical background, language, culture, customs, etc. The technique used in the stories is good. Having the meaning of the words in their own language helps the reader to understand the story.